Frequency, trends and institutional variation in 30‐day all‐cause mortality and unplanned readmissions following hospitalisation for heart failure in Australia and New Zealand. (9th November 2020) - Labrosciano, Clementine; Horton, Dennis; Air, Tracy; Tavella, Rosanna; Beltrame, John F.; Zeitz, Christopher J.; Krumholz, Harlan M.; Adams, Robert J.T.; Scott, Ian A.; Gallagher, Martin; Hossain, Sadia; Hariharaputhiran, Saranya; et al.
Abstract: Aims: National 30‐day mortality and readmission rates after heart failure (HF) hospitalisations are a focus of US policy intervention and yet have rarely been assessed in other comparable countries. We examined the frequency, trends and institutional variation in 30‐day mortality and unplanned readmission rates after HF hospitalisations in Australia and New Zealand. Methods and results: We included patients >18 years hospitalised with HF at all public and most private hospitals from 2010–15. The primary outcomes were the frequencies of 30‐day mortality and unplanned readmissions, and the institutional risk‐standardised mortality rate (RSMR) and readmission rate (RSRR) evaluated using separate cohorts. The mortality cohort included 153 592 patients (mean age 78.9 ± 11.8 years, 51.5% male) with 16 442 (10.7%) deaths within 30 days. The readmission cohort included 148 704 patients (mean age 78.6 ± 11.9 years, 51.7% male) with 33 158 (22.3%) unplanned readmission within 30 days. In 392 hospitals with at least 25 HF hospitalisations, the median RSMR was 10.7% (range 6.1–17.3%) with 59 hospitals significantly different from the national average. Similarly, in 391 hospitals with at least 25 HF hospitalisations, the median RSRR was 22.3% (range 17.7–27.1%) with 24 hospitals significantly different from the average. From 2010–15, the adjusted 30‐day mortality [odds ratio (OR) 0.991/month, 95% confidence interval (CI) 0.990–0.992, P  < 0.01] and unplanned readmission (OR 0.998/month, 95% CI 0.998–0.999, P  < 0.01) rates declined. Conclusion: Within 30 days of a HF hospitalisation, one in 10 patients died and almost a quarter of those surviving experienced an unplanned readmission. The risk of these outcomes varied widely among hospitals suggesting disparities in HF care quality. Nevertheless, a substantial decline in 30‐day mortality and a modest decline in readmissions occurred over the study period. Abstract : In this population‐wide study of early outcomes following heart failure (HF) hospitalisations in Australia and New Zealand, we found that one in 10 patients died, and almost a quarter experienced an unplanned readmission, within 30 days. We also observed a significant decline in 30‐day all‐cause mortality and a modest reduction in readmissions over the study period despite the absence of broad policy efforts to improve HF outcomes. However, 30‐day mortality and unplanned readmission rates varied two to threefold among hospitals suggesting disparities in care quality, highlighting the need for coordinated efforts to standardise care.